Analysis of Economic Crisis and Reforms In India of 1991: Analyzing the Economic Crisis and Reforms in India (1991) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Inpost-Independence India, the Central Government pursued a policy of mixedeconomy which bore no expected results. The economy grew with so slow pace thatK.N. Raj coined it with the term “Hindu rate of growth” which was around 3% perannum. With the growth of the population, that of welfare activities of theGovernment and its conspicuous consumption, the economy of the country wasconfronted with a deep and alarming economic crisis which warranted immediateeconomic reforms in 1991. The present article seeks to analyse the crisis andthe efforts made by the Government of India to avert the crisis througheconomic reforms in 1991.